2013
DOI: 10.1590/s0102-311x2013000700014
|View full text |Cite
|
Sign up to set email alerts
|

The association between geographical factors and dental caries in a rural area in Mexico

Abstract: The aim of this study was to investigate the association between markers of oral disease and geographical factors influencing access to dental care (DMFT score) among school children in Central Mexico. Retrospective data were collected during an international service-learning program between 2002 and 2009. A sample of 1,143 children (55% females; mean age 12.7±13.1years) was analyzed. The mean DMFT score, represented largely by untreated tooth decay, was 4.02 (4.76). The variables that had the most significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
1
21
1
3
Order By: Relevance
“…Several studies of rural Mexican communities have shown a varying prevalence of caries, ranging from 43% to 100%. It is notable that that not all of these studies used the same caries index. Our results showed no statistical differences between male and female students; this is in contrast to other studies on Mexican adolescents that showed a higher prevalence of caries in female subjects.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Several studies of rural Mexican communities have shown a varying prevalence of caries, ranging from 43% to 100%. It is notable that that not all of these studies used the same caries index. Our results showed no statistical differences between male and female students; this is in contrast to other studies on Mexican adolescents that showed a higher prevalence of caries in female subjects.…”
Section: Discussioncontrasting
confidence: 91%
“…The location inhabited by this community is consistent with that of other Latin American indigenous populations who are often relegated to less desirable lands – mountains and jungle instead of proximity to rivers and flatlands. The isolation of these communities plays a role in their ethnic homogeneity and on the narrow range of socio‐economic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…one can imagine that a third-order, hybrid, high-impact course is ideal for social work students who intend to enter careers focused on studying and conducting research on the effectiveness of various types of community initiatives or intervention programs directed at particular groups; community nursing students who are interested in a career that includes research on a community health issue in special populations; psychology students who want to pursue careers in which they conduct research on community issues related to social justice and policy for underrepresented groups; or engineering or science students who want to conduct research on an environmental issue (e.g., solar energy in remote sites, conducting research to efficiently improve water quality in an international setting) in a particular geographic region after graduation. The Indiana University School of Dentistry has dental students working with Mexican dental students on research that contributes to local knowledge about oral health issues, enhances the U.S. students' understanding of how context and culture are factors in oral health, enhances intercultural competency, and provides all students with opportunities to improve their research skills (Maupome et al, 2013).…”
Section: Pcar Immersive Cipp Pcar Immersive Cippmentioning
confidence: 99%
“…Además, es la necesidad de salud más frecuentemente no cubierta en preescolares, escolares y adolescentes de Latinoamérica, sobre quienes se observa poca experiencia de tratamiento dental restaurador [3][4][5][6] . Específicamente en México, la caries dental representa el principal problema de salud pública bucal; por ejemplo, en la dentición permanente entre el 70 y 85% de la población escolar a los 12 años de edad presenta esta enfermedad [7][8][9][10] . Constituye, por otro lado, la primera causa de mortalidad dental en varios grupos de edad 11 representando un importante desafío para el sistema de atención a la salud bucal, debido a los altos costos de atención.…”
Section: Introductionunclassified